The evaluation of sunnah and non-sunnah eating manners among young Muslim generation and their effects on comfort practices and satiety level: case study in Kuantan, Pahang - Abu Bakar, Ibrahim; Ab Rahim, Rafidah (USIM Press, 2021)
This study evaluated sunnah and non-sunnah eating manners among young Muslim generation in Kuantan, Pahang involving secondary school children (age between 13-17) and university students (age between 18-25 years old). The sunnah and non-sunnah eating manners were cross-sectional studied and their effect on comfort practices and satiety levels were examined. About 200 respondents were voluntarily participated in this study where the data were collected using specific and pre-tested questionnaire. The level of comfort practices and satiety were measured using 1-5 Likert scale and all data were statistically analysed using computer software program; Statistical Package for Social Science (SPSS) version 21. The results show that among sunnah eating practices which got high percentage score are recite doa before eating (84.0%), take closest food first (67.0%) and wash hand after eating (61.5%). While among non-sunnah eating practices which frequently practiced by respondents are eat while watching TV or reading (37.5%), blowing onto hot food (35.0%) and bring up plate close to mouth when eating (31.0%). Most practices of sunnah eating manners are influenced at least by one demographic factors either education level, age, gender and parenting factors. Many of non-sunnah eating manners are practiced by respondents on their own and not influenced by demographic factors. The results also show that sunnah eating manners are more comfortable to be practiced than non-sunnah eating manners and sunnah eating manners can give full satisfaction where the eater can achieve full satiety level where non-sunnah eating manners just give fullness feeling. This study shows a lot of wisdoms behind practices of sunnah eating manners